Impact of family and work conflicts on job satisfaction, life satisfaction and health of female teachers in Ethiopia: the moderating role of resilience - Enaney Wondem Misfin; Manjit Singh; Shivinder Phoolka (Cogent Business & Management, 2024)
Family and work are essential components of modern life in both advanced and developing societies. Devoting excessive time to one of these domains' conflicts with the other; they are interdependent and crucial to existence. Based on spillover and role theory, this study examines the impact of family–work and work–family conflict on job satisfaction, life satisfaction, and mental and physical health. Moreover, the research examines whether or not resilience moderates this association. In a cross-sectional design, a sample of 242 married female high school teachers administered a questionnaire. The study used the most recent PLS-SEM (partial least square structural equation modeling) software for data analysis. According to the findings, family–work conflict has a negative and statistically significant impact on job and life satisfaction. Work–family conflict, on the other hand, has a significant positive effect on life satisfaction. The results also revealed that both family–work and work–family conflicts have insignificant effects on mental and physical health. Moreover, the research showed that resilience plays a moderating role in the association between family–work conflict and both job and life satisfaction. This study contributed an additional understanding of the impacts of work and family conflict and aids policymakers and the Ministry of Education in developing efficient family-friendly policies.
Keywords: 650; Family-work conflict; work-family conflict; job satisfaction; life satisfaction; health; resilience